2019
DOI: 10.1136/bmjopen-2019-030234
|View full text |Cite
|
Sign up to set email alerts
|

Can risk be predicted? An umbrella systematic review of current risk prediction models for cardiovascular diseases, diabetes and hypertension

Abstract: ObjectiveTo provide an overview of the currently available risk prediction models (RPMs) for cardiovascular diseases (CVDs), diabetes and hypertension, and to compare their effectiveness in proper recognition of patients at risk of developing these diseases.DesignUmbrella systematic review.Data sourcesPubMed, Scopus, Cochrane Library.Eligibility criteriaSystematic reviews or meta-analysis examining and comparing performances of RPMs for CVDs, hypertension or diabetes in healthy adult (18–65 years old) populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…This revealed that clear evidence is present only for the prediction of CVD; the Framingham score, by itself or in association with the Ankle-Brachial Index, and QRISK score can be considered as the gold standard. Further efforts must not be focused on the production of new scores but should, instead, focus on the external validation of existing scores, particularly in groups at high risk (Lucaroni et al, 2019). Results of this study and similar studies should add to the validation and/or modification of the RPMs that are currently available.…”
Section: Discussionmentioning
confidence: 99%
“…This revealed that clear evidence is present only for the prediction of CVD; the Framingham score, by itself or in association with the Ankle-Brachial Index, and QRISK score can be considered as the gold standard. Further efforts must not be focused on the production of new scores but should, instead, focus on the external validation of existing scores, particularly in groups at high risk (Lucaroni et al, 2019). Results of this study and similar studies should add to the validation and/or modification of the RPMs that are currently available.…”
Section: Discussionmentioning
confidence: 99%
“…inattention (InA) and hyperactivity (HA). These types of questions of a best genetic predictor of an outcome trait or disease may come up in multiple contexts, such as the prediction of educational attainment by cognitive ability and non-cognitive skills (Demange et al 2020 ) or hypertension and cardiovascular outcomes by multiple correlated factors (Lucaroni et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, in addition to IL-6 SNP, arterial hypertension was associated with type 2 diabetes mellitus. Studies have demonstrated that cardiovascular diseases, hypertension and diabetes are strongly correlated to each other[ 73 ]. Their powerful relationship have also been observed in patients chronically infected with HCV[ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%